Measuring Malnutrition and Intestinal Helminthiasis on Tobacco Plantation Workers’ Children - Chairuddin P. Lubis; Helena Siregar; Alogo Siregar; Ratna Maulana Lubis (Paediatrica Indonesiana, 1979)
Assessment of nutritional status and fecal examination for intestinal helminthiasis were conducted on 317 children of Tobacco Plantation workers. The nutritional status was measured by using the "three coloured cord" and fecal examination was done by the direct smear method with the result 15.14% of the children suffered from severe malnutrition, 44.80% possible mild malnutrition and 40.06% were normal. Fecal examination revealed that 64.90% had Ascariasis, 20.20% had Trichuriasis, 4.33% had Oxyuriasis.